INFLUENCE OF VILLAGE FINANCIAL SYSTEM, APPARATUS COMPETENCY, AND INTERNAL CONTROL SYSTEM ON THE QUALITY OF FINANCIAL STATEMENTS - Irmawati Ibrahim; Marwah Yusuf; Rahman Pura (Institut Transparansi dan Akuntabilitas Publik (INSPIRING), 2021)
Purpose – This study aims to determine the effect of the village financial system, apparatus competence and internal control system on the quality of financial reports in the Village government in Adonara Tengah District, East Flores Regency, East Nusa Tenggara province. Design/methodology/approach – Methods of data collection using primary data obtained from a questionnaire using a saturated sampling technique. The population of this study were all 65 village officials in Adonnara Tengah subdistrict, East Flores district, while the sample taken was 65 respondents. The results of the questionnaire have been tested for validity and reliability, and classical assumptions have been tested in the form of normality assumptions, multicollinearity assumptions and heteroscedasticity assumptions. Findings – The data analysis method used multiple linear regression.The results show that the village financial system has a significant positivve effect on the quality of financial reports, the competence of the apparaturs does not effect the quality of financial reports and the internal control system has a significant positive effect on the quality of financial reports. Keywords: Village Financial System, Apparatus Competence, Internal Control System, Quality of Financial Statements Paper type Article Text